Answer:
12)
11)
10)
9)
8)
7)
6)
5)
4)
3)
2)
1)
Explanation:
12)
y - 4 = −(x - 4)
y - 4 = −x + 4
+ 4 + 4
__________
_____________________________________________
11)
y + 2 = 12(x + 2)
y + 2 = 12x + 24
- 2 - 2
____________
_____________________________________________
10)
y - 1 = 5(x - 1)
y - 1 = 5x - 5
+ 1 + 1
_________
_____________________________________________
9)
y - 5 = −2(x + 2)
y - 5 = −2x - 4
+ 5 + 5
__________
_____________________________________________
8)
y - 5 = 2(x + 2)
y - 5 = 2x + 4
+ 5 + 5
__________
_____________________________________________
7)
y + 4 = 12(x - 2)
y + 4 = 12x - 24
- 4 - 4
____________
_____________________________________________
6)
4x - 3y = −6
-4x - 4x
________
−3y = −4x - 6
___ _____
−3 −3
_____________________________________________
5)
4x - y = 2
-4x - 4x
_______
−y = −4x + 2
_____________________________________________
4)
x - y = 0
______
−y = −x
_____________________________________________
3)
7x - 5y = 35
-7x - 7x
_________
−5y = −7x + 35
___ ______
−5 −5
_____________________________________________
2)
2x - y = 4
-2x - 2x
_______
−y = −2x + 4
_____________________________________________
1)
2x - 3y = 24
-2x - 2x
_________
−3y = −2x + 24
___ _______
−3 −3
I am delighted to assist you anytime.